Circumcision as an Intervening Strategy against HIV Acquisition in the Male Genital Tract - Lakhikumar Sharma, Adhikarimayum; Hokello, Joseph; Tyagi, Mudit (Pathogens, 2021)
Unsafe sex with HIV-infected individuals remains a major route for HIV transmission, and protective strategies, such as the distribution of free condoms and pre-or post-prophylaxis medication, have failed to control the spread of HIV, particularly in resource-limited settings and high HIV prevalence areas. An additional key strategy for HIV prevention is voluntary male circumcision (MC). International health organizations (e.g., the World Health Organization, UNAIDS) have recommended this strategy on a larger scale, however, there is a general lack of public understanding about how MC effectively protects against HIV infection. This review aims to discuss the acquisition of HIV through the male genital tract and explain how and why circumcised men are more protected from HIV infection during sexual activity than uncircumcised men who are at higher risk of HIV acquisition.
Keywords: HIV; viral transmission; circumcision; heterosexual HIV-1 transmission